2023
DOI: 10.1002/bsl.2607
|View full text |Cite
|
Sign up to set email alerts
|

Violence risk assessment of Sovereign Citizens: An exploratory examination of the HCR‐20 Version 3 and the TRAP‐18

Abstract: Sovereign Citizens comprise an understudied right‐wing extremist movement in the United States who have grown in notoriety in recent years due to several high‐profile instances of violence. Despite this, little empirical research has been conducted on Sovereign Citizens, including research on assessing their risk for violence. In this study, we sought to replicate and extend a prior study on Sovereign Citizen violence. Using open‐source data, we added several new cases to a pre‐existing dataset of violent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Eight of the distal characteristics were identified retroactively in the case of NC. Vargen and Challacombe (2023) investigated 83 cases of violent and nonviolent Sovereign Citizen incidents, using the TRAP-18. Their findings "indicated that higher scores … were significantly associated with greater odds of cases being violent" (p. 55).…”
Section: Discussionmentioning
confidence: 99%
“…Eight of the distal characteristics were identified retroactively in the case of NC. Vargen and Challacombe (2023) investigated 83 cases of violent and nonviolent Sovereign Citizen incidents, using the TRAP-18. Their findings "indicated that higher scores … were significantly associated with greater odds of cases being violent" (p. 55).…”
Section: Discussionmentioning
confidence: 99%
“…Warning behaviors should compel a sense of urgency in those assessing and risk managing subjects of concern. (p. 8) TRAP-18 research has so far indicated both high sensitivity and high specificity (Böckler et al, 2020;Vargen & Challacombe, 2022).…”
Section: Nexus Of Psychopathology and Ideologymentioning
confidence: 99%
“…Meanwhile, an independent research group investigated sovereign citizens, an antigovernment nationalist collective in the United States, with the TRAP-18 in two studies (Challacombe & Lucas, 2019; Vargen & Challacombe, 2023). In the first study (Challacombe & Lucas, 2019), subjects ( n = 30) who planned or committed violent actions were compared to subjects ( n = 28) who committed nonviolent criminal actions.…”
Section: Last Resort Correlates With and Postdicts Targeted Attacksmentioning
confidence: 99%
“…This was the first postdictive study of a U.S. domestic terrorism group. In the second study (Vargen & Challacombe, 2023), the sovereign citizen sample was increased to 107 cases, and the TRAP-18 was coded alongside the HCR-20 V3 Historical scale. Higher coding on both instruments was associated with greater odds of being violent.…”
Section: Notementioning
confidence: 99%